2007
DOI: 10.1007/s10540-007-9050-3
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Dependent Different Action of Tamoxifen on Membrane Fluidity

Abstract: Tamoxifen (TAM) is a non-steroidal antiestrogen drug, which is widely used to prevent and treat breast, liver, pancreas and brain cancers. The present work investigates, in detail, the concentration dependent behavior of TAM (varying from 1 mol% to 45 mol%) on membrane fluidity. The differential scanning calorimetry (DSC) studies showed that tamoxifen eliminates the pre-transition and decreases the main phase transition to lower temperatures. Using visible spectroscopy at 440 nm and Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Assessments made through fluorescence polarization, DSC and turbidity are concurrent with the findings referred above, indicating that tamoxifen causes higher acyl chain disorder and, therefore, increased membrane fluidity in DMPC, DPPC and DSPC model membranes [97][98][99]. chains and present a weak cytotoxic activity [106].…”
Section: Studies Using Dsc and Langmuir Isotherms Demonstrated That Psupporting
confidence: 59%
“…Assessments made through fluorescence polarization, DSC and turbidity are concurrent with the findings referred above, indicating that tamoxifen causes higher acyl chain disorder and, therefore, increased membrane fluidity in DMPC, DPPC and DSPC model membranes [97][98][99]. chains and present a weak cytotoxic activity [106].…”
Section: Studies Using Dsc and Langmuir Isotherms Demonstrated That Psupporting
confidence: 59%
“…Thus, tamoxifen at high doses (10 M) caused lysis (necrosis) of almost all cells within 24 h that cannot be prevented by estradiol . The cytotoxic action of tamoxifen may result from perturbations in membrane fluidity (Kazanci and Severcan, 2007), formation of reactive oxygen species (Nazarewicz et al, 2007), DNA damage by DNA-adducts or chromosomal aberrations, which have been found to occur in kidney and liver (Han and Liehr, 1992;Sargent et al, 1994). On the other hand, lower concentrations of tamoxifen (1 M and below) induced a gradual appearance of cell death starting to occur approximately 2-3 days after treatment .…”
Section: Autophagic Cell Deathmentioning
confidence: 99%
“…Biological membranes are composed of extremely complex structures; thus, model membranes provide a highly convenient, simple method for studying drugmembrane interactions (Bangham, 1972;Engberts and Hoekstra, 1995;Kazanci and Severcan, 2007;Severcan et al, 2005). Despite its importance, studies on the interaction of celecoxib with membranes at a molecular level are very limited.…”
mentioning
confidence: 99%